The Effect of Physical Activity in Decreasing the Level of Fatigue for Patients with Multiple Sclerosis - Abu-Malluh, Dema Ibrahim; Al Nahar , Hazem Nouri (Dirasat: Educational Sciences, 2020)
The aim of this study was to assess the effect of physical activity in decreasing the level of fatigue for patients with Multiple Sclerosis. The descriptive method was used for this study. The study sample consisted of 80 patients with Multiple Sclerosis from the health insurance center in Amman. A questionnaire was used in this study to measure the effect of fatigue on Multiple Sclerosis. The researcher used the following statistical analysis: Cronbach Alpha, Mean, Standard Deviation, Frequency, Independent sample t- test, one way Anova and Post-hoc. The results showed that there was no significant difference between males and females in the severity of fatigue. There was no significant difference in the severity of fatigue for patients with multiple sclerosis of different ages. The results showed that the longer the duration of disease, the worse the fatigue severity. Finally, the results showed that the severity of fatigue among patients with multiple Sclerosis was lower for those who were physically active compared to those who were less active. The researcher recommends patients with Multiple Sclerosis to perform physical activity to decrease the severity of fatigue.